(untitled) (Research, Society and Development, 2023)
Pesticides impact the entire ecosystem and can remain in the environment for decades. These substances are related to a series of diseases and health problems and can be present in soil, water, air, fresh or processed foods, animal tissue and breast milk. Therefore, the objective was to carry out a bibliographical survey bringing together works relating to the impacts on health, the environment and biodiversity generated by the use of pesticides in agriculture. To this end, databases such as: Google Scholar, Scientific Electronic Library Online - Scielo, Medical Literature Analysis and Retrieval System – MEDLINE/Pubmed and Periódicos Capes were accessed in order to search for indexed articles and works, using keywords. After reading the materials found, files in Portuguese, English and Spanish with relevance to the topic to be discussed were pre-selected and subsequently used as a database in writing the review. It was concluded that the intensive use of pesticides has several consequences, which may affect health, the environment, biodiversity and the ecosystem. Acute and chronic illnesses can arise from pesticide poisoning. Producers with a low level of education tend to impact the proper reading of pesticide labels and care regarding the use of PPE, increasing the number of poisoning cases. With the increase in female representation in agriculture, susceptibility to problems related to the use of pesticides, such as fetal malformation and abortion, has increased, in addition to the fact that exposure to pesticides can have harmful effects on the human immune system.